Pengembangan E-LKPD Berbasis Liveworksheet Berbantuan Quizwhizzer Pada Materi Kegiatan Ekonomi Kelas V SD Negeri 7 Kampungdalem Kabupaten Tulungagung - Khoiru Rifai; Aditya Pringga Satria (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This research aims to develop an electronic student worksheet (E-LKPD) based on Liveworksheet, integrated with Quizwhizzer, for teaching economic activities in elementary school. The background of this study stems from the limited variation in learning activities and the underutilization of digital technology in the learning process at schools. To address these problems, the study seeks to produce innovative, interactive, and easily accessible learning media that can support student engagement and improve learning outcomes. The development process follows the ADDIE model, consisting of five stages: Analyze, Design, Development, Implementation, and Evaluation. In the analysis stage, the needs of students and teachers were identified. The design and development stages involved creating E-LKPD content integrated with Liveworksheet and interactive quizzes using Quizwhizzer. The implementation was carried out through classroom trials, followed by evaluation to assess the effectiveness and feasibility of the product. Data collection was conducted through expert validation (media, material, and language experts) and questionnaire responses from both teachers and students. The validation results indicated that the E-LKPD developed is of excellent quality, with a score of 90% from media experts, 98% from material experts, and 96% from linguists. The student trial also produced highly positive results, with a feasibility score of 83%, reflecting strong student enthusiasm and acceptance of the media. Teachers also responded positively to the practicality and clarity of the content. Based on these results, it can be concluded that the Liveworksheet-based E-LKPD integrated with Quizwhizzer is highly feasible and effective for use in teaching economic activities at SD Negeri 7 Kampungdalem. This learning media is expected to increase students' interest, motivation, and active participation, while also optimizing the role of technology in supporting a more engaging and meaningful learning experience in the classroom.